The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1109/tnb.2014.2343237
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Target Tracking by a Mobile Bionanosensor Network

Abstract: This paper describes a mobile bionanosensor network designed for target tracking. The mobile bionanosensor network is composed of bacterium-based autonomous biosensors that coordinate their movement through the use of two types of signaling molecules, repellents and attractants. In search of a target, the bacterium-based autonomous biosensors release repellents to quickly spread over the environment, while, upon detecting a target, they release attractants to recruit other biosensors in the environment toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 35 publications
1
56
0
Order By: Relevance
“…Similarly, anisotropy can be taken into account by changing the rates in (1) for different directions. We are currently investigating the analysis in instances where distinct bacterial populations use quorum sensing signaling to enhance exchange of environmental information (e.g., as discussed in [30]). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, anisotropy can be taken into account by changing the rates in (1) for different directions. We are currently investigating the analysis in instances where distinct bacterial populations use quorum sensing signaling to enhance exchange of environmental information (e.g., as discussed in [30]). …”
Section: Resultsmentioning
confidence: 99%
“…Thornlow et al [28] show that increasing the motility of anerobic bacteria, Salmonella and generating homogeneous population of highly motile Salmonella, enhanced tumor penetration in vitro. Okaie et al [30] developed a microsensor network equivalent of bacterial chemotaxis. They exploited the model in [31] (later extended in [32]) where bacteria were modeled as microsensors and base stations were placed to monitor the different sensors.…”
Section: Introductionmentioning
confidence: 99%
“…Information may be encoded in DNA strands and then transported by flagellated bacteria [46]. Attractant and repellent molecules are sometimes used to drive bacteria to the receiver [54].…”
Section: Other Modelsmentioning
confidence: 99%
“…One approach to modeling the target tracking scenario described above is to use individual-based models [20]. For example, a bacterium-based self-propelling biosensor (i.e., bionanomachines in our definition) may be modeled as an individual object with a direction of movement θ and the constant velocity v (Fig.…”
Section: Overviewmentioning
confidence: 99%
“…Our early efforts introduced, for the first time in the area of nanoscale and molecular networking, the problem of target tracking using molecular communication, developed an individual-based model, and demonstrated that a group of bio-nanomachines interacts through the use of attractants and repellents to track moving targets [20]. While the individualbased modeling approach provides flexibility in modeling individual behaviors, the computational cost is expensive and does not scale to the number of individuals (e.g., the number of bio-nanomachines and targets).…”
Section: Introductionmentioning
confidence: 99%